Causal relationship between beta-2 microglobulin and B-cell malignancies: genome-wide meta-analysis and a bidirectional two-sample Mendelian randomization study - Li, Jiuling; Wu, Yao; Zhang, Xin; Wang, Xueju (Frontiers in Immunology, 2024)
Background: Beta-2 microglobulin (β2M) is acknowledged as a prognostic biomarker for B-cell malignancies. However, insights into the impact of β2M on B-cell malignancy risk, and vice versa, are limited. Methods: We conducted a genome-wide meta-analysis (GWMA), bidirectional two-sample Mendelian randomization (TSMR) analysis, and pathway enrichment analysis to explore the causal relationship between β2M and B-cell malignancies and the underlying biological processes. Results: The GWMA identified 55 lead SNPs across five genomic regions (three novel: WDR72, UMOD, and NLRC5) associated with β2M. In the UKB, genetically predicted β2M showed a positive association with diffuse large B-cell lymphoma (DLBCL; odds ratio [OR]: 1.742 per standard deviation increase in β2M; 95% confidence interval [CI]: 1.215–2.498; P = 3.00 × 10−3; FDR = 7.50× 10−3) and Hodgkin lymphoma (HL; OR: 2.270; 95% CI: 1.525–3.380; P = 5.15 × 10−5; FDR =2.58 × 10−4). However, no associations were found with follicular lymphoma (FL), chronic lymphoid leukemia (CLL), or multiple myeloma (MM). Reverse TSMR analysis revealed no association between genetically predicted B-cell malignancies and β2M. In FinnGen, β2M was found to be associated with an increased risk of DLBCL (OR: 2.098; 95% CI: 1.358-3.242; P = 8.28 × 10−4; FDR = 4.14 × 10−3), HL (OR: 1.581; 95% CI: 1.167-2.142; P = 3.13 × 10−3; FDR = 5.22 × 10−3), and FL (OR: 2.113; 95% CI: 1.292-3.455; P = 2.90 × 10−3; FDR = 5.22 × 10−3). However, no association was found with CLL or MM. Reverse TSMR analysis indicated that genetically predicted DLBCL, FL, and MM may perturb β2M levels. Pathway enrichment analysis suggested that the innate immune system represents a convergent biological process underlying β2M, DLBCL, and HL. Conclusions: Our findings suggested that elevated levels of β2M were associated with an increased risk of DLBCL and HL, which is potentially linked to dysfunction of the innate immune system.